Uma nova era para Quercus spp.: sustentabilidade de recursos naturais subvalorizados - Ferreira da Vinha, Ana (2021)
The genus Quercus spp. belongs to the family Fagaceae, being widespread throughout the Northern Hemisphere. Quercus fruits (acorns) play an important role on the rural economy for animal feeding. However, their nutri!onal value and high phytochemical contents have raised the interest of many researchers looking for underu!lized foods to integrate the human diet. Previous studies highlighted acorns as a rich natural source of essen!al nutrients and individual phytochemicals with an!oxidant, an! tumoral and cardioprotec!ve proper!es. Other reports inclusively described their use in folk medicine for the treatment of atherosclerosis, diabetes and Alzheimer’s disease. At the industrial level, some Quercus spp. fruits are already used as edible oil and flour, but a wide diversity of other specialty products could be developed. Accordingly, the comprehensive characteriza!on of these fruits may lead to an increase in their added value for further applica!ons in several industries, such as food, pharmaceu!cal, or cosme!cs, genera!ng addi!onal profits and, essen!ally, improving social, economic and environmental sustainability.